Effect of thickness gradient on creep behaviour in a rotating composite disc - Singh, Jaskaran (My University, 2013)
The creep behaviour of a rotating disc having variable thickness and made of isotropic aluminium-silicon carbide particulate composite has been investigated. The stress and strain rates in the disc have been obtained by using threshold stress based creep law. A computer code based on the mathematical analysis is developed to obtain creep response of rotating composite disc. Different thickness profiles have been considered to investigate their effect on stresses and strains are compared. The effects of changing the particle size of reinforcement have also been investigated.
Master of Engineering, Thesis
Keywords: Composite; Thickness Gradient; Rotating Disc; Creep